Variation in hemolytic activity of Brachyspira hyodysenteriae strains from pigs. (December 2016) - Mahu, Maxime; De Pauw, Nele; Vande Maele, Lien; Verlinden, Marc; Boyen, Filip; Ducatelle, Richard; Haesebrouck, Freddy; Martel, An; Pasmans, Frank
Abstract Brachyspira hyodysenteriae is the primary cause of swine dysentery, which is responsible for major economic losses to the pig industry worldwide. The hemolytic activity of 10B. hyodysenteriae strains isolated from stools of pigs with mild to mucohemorrhagic diarrhea was compared and seven hemolysis associated genes were sequenced. Hemolysis induced by these strains varied from strong to near absent. One weakly hemolyticB. hyodysenteriae strain showed sequence changes in five hemolysis associated genes (tlyA, tlyB, hemolysin III, hemolysin activation protein andhemolysin III channel protein ) resulting in amino acid substitutions. The occurrence of weakly hemolytic strains identifiable asB. hyodysenteriae should be taken into account in swine dysentery diagnostics. The presence of these strains may affect herd dysentery status, with great impact on a farms trading opportunities.